Evaluasi Mutu Fisik, Uji Kelembapan dan Potensi Aktivitas Tabir Surya Pelembab Bibir Ekstrak Etanol Daun Pucuk Merah (Syzygium myrtifolium Walp.) - Safitri , Nurhaliza; Yuniarti , Rafita; Dalimunthe , Gabena Indrayani; Lubis , Minda Sari (Journal of Pharmaceutical and Sciences, 2025)
Background: Lip balm is a cosmetic preparation containing key components such as waxes, fats, and oils—derived from either natural or synthetic extracts—to prevent lip dryness by enhancing moisture and protecting against harmful environmental factors. The red shoot plant (Syzygium myrtifolium Walp.) is commonly known as an ornamental plant but also contains beneficial chemical compounds. Objective: This study aims to formulate red shoot leaf ethanol extract into a lip balm with good physical quality, sun protection capability, and moisturizing effects. Methods: This research uses an experimental method with quantitative and qualitative data collection. The stages include simplicia characterization, secondary metabolite identification, extract preparation through maceration, lip balm formulation, and evaluation of physical quality (organoleptic test, homogeneity, pH, stability, irritation, melting point, and hedonic test), moisture test, and Sun Protection Factor (SPF) value determination. Results: The red shoot leaf extract was successfully formulated into a stick lip balm at concentrations of 5%, 7%, and 10%. The formulas demonstrated good physical quality in all tests, increased lip moisture and oil content (especially at 10% concentration), and high SPF values with ultra protection at the 10% concentration. Conclusion: Red shoot leaf extract (Syzygium myrtifolium Walp.) can be used as an active ingredient in lip balm, providing optimal physical quality, moisturizing effects, and UV radiation protection.